2013
DOI: 10.1016/j.joep.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Lying and team incentives

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
156
7
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 26 publications
15
156
7
4
Order By: Relevance
“…These additional analyses confirm that oxytocin drives dishonesty when it serves one's group, but not when it only serves personal self-interest. Moreover, and as seen in other work (22), these additional analyses show that this oxytocin-motivated group-serving dishonesty manifests itself especially in extreme lies.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These additional analyses confirm that oxytocin drives dishonesty when it serves one's group, but not when it only serves personal self-interest. Moreover, and as seen in other work (22), these additional analyses show that this oxytocin-motivated group-serving dishonesty manifests itself especially in extreme lies.…”
Section: Resultssupporting
confidence: 82%
“…Indeed, in her testimony, the mother indicated that she deliberately took the risk of punishment to improve her children's chances in life (20). Such motivation to serve others, it stands to reason, is more powerful and makes it easier to generate justification for moral code breaking than a motivation to serve personal interests only (even when holding personal profit constant) (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…This is confirmed by a Kolmogorov-Smirnov test on average reported profit levels (p = 0.047). Hence, we support the gender differences predominately found in the literature (e.g., Dreber and Johannesson, 2008;Houser et al, 2012;Conrads et al, 2013).…”
Section: The Impact Of Gender and Svo On Honestysupporting
confidence: 90%
“…We condition SVO types on individualists and prosocials as we could not identify any altruists and only one competitive type. 10 Subjects report an average a profit level of 3.19 which is similar to previous finding of Conrads et al (2013) who played a die game with higher stake size. 11…”
Section: The Impact Of Gender and Svo On Honestysupporting
confidence: 81%
“…2008; Childs, 2012;Erat and Gneezy, 2012;Houser et al, 2012;Conrads et al, 2013Conrads et al, , 2014Abeler et al, 2014). 1 So far, the literature on lying behavior has mainly analyzed decisions by individuals; possibly in strategic interaction with other individuals as in tournaments (see e.g., Conrads et al, 2014).…”
Section: Introductionmentioning
confidence: 99%